2010
DOI: 10.1614/wt-d-09-00058.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oriental Mustard (Brassica juncea) Seed Meal for Weed Suppression in Turf

Abstract: Oriental mustard seed meal (MSM), a byproduct generated by pressing the seed for oil, exhibits herbicidal properties. In turfgrass, soil fumigants such as methyl bromide are used to control weeds prior to renovation of turf. Environmental concerns have resulted in deregistration of methyl bromide, prompting the need for alternatives. The objective of this research was to determine the effect of MSM on the establishment of selected turfgrass weeds as well as inhibitory effects on establishment of desirable turf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Although MSM suppresses weed emergence and growth, it also can negatively affect crop seed germination and growth (Rice, Johnson-Maynard, Thill, & Morra, 2007;Earlywine, Smeda, Teuton, Sams, & Xiong, 2010;Boydston, Morra, Borek, Clayton, & Vaughn, 2011). MSM derived from Sinapis alba applied to the soil at 2.2 and 4.5 MT ha -1 reduced weed emergence by 76 to 91% for a period of 4 wks in onion (Allium cepa) (Boydston et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although MSM suppresses weed emergence and growth, it also can negatively affect crop seed germination and growth (Rice, Johnson-Maynard, Thill, & Morra, 2007;Earlywine, Smeda, Teuton, Sams, & Xiong, 2010;Boydston, Morra, Borek, Clayton, & Vaughn, 2011). MSM derived from Sinapis alba applied to the soil at 2.2 and 4.5 MT ha -1 reduced weed emergence by 76 to 91% for a period of 4 wks in onion (Allium cepa) (Boydston et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Plants of the Brassicaceae, or crucifer family, have been utilized as cover crops and green manures for decades because of their ability to suppress crop pests such as weeds, nematodes, insects, and soil-borne pathogens (Earlywine et al, 2010). Incorporation of Brassicaceae tissues into the soil also provides other ecological services such as nutrient recycling, moisture retention, improvement of soil tilth, and mitigation of erosion (Bangarwa, 2011).…”
Section: Brassicaceae Plantsmentioning
confidence: 99%
“…One study showed that soil amendment with brown mustard seed meal successfully suppressed the emergence of several weeds species including large crabgrass, annual bluegrass (Poa annua), buckhorn plantain (Plantago lanceolata), white clover (Trifolium repens), and common chickweed (Stellaria media) by 63% or more (Earlywine, 2010).…”
Section: Watercress Turnip and Mustardmentioning
confidence: 99%
See 2 more Smart Citations